A mobile plataform with a catadioptric sensor - Tommaselli, A. M.G. [UNESP]; Marcato Junior, J.; Olivete, A. L.; De Moraes, M. V.A. [UNESP] (Copernicus Publications, 2014)
The aim of this paper is to present a mobile catadioptric omnidirectional vision system composed of a camera and a cone-shaped mirror integrated with a direct georeferencing system. The relationship between image and object space is established with generic/empiric or physical models. The models were implemented and tested with real data and some results are presented. The results showed that accuracies around 5 cm in planimetry can be achieved, which is suitable for several applications, including the generation of control scenes that was the original motivation of this work.
Keywords: Mapping; Mobile; Modelling; Orientation; Sensor